2020
DOI: 10.1111/raq.12459
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium butyricum: a promising probiotic confers positive health benefits in aquatic animals

Abstract: Clostridium butyricum is a bacterium of rod shape, strictly anaerobic, Gram‐positive and form spores. Short‐chain fatty acids, biofuel compounds and precursors of biomaterials (H2, butanol and 1,3‐propanediol) are produced by C. butyricum during the fermentation of carbohydrates and sugars. In humans and animals, although C. butyricum has been found to be associated with botulism in infant and necrotising enterocolitis in preterm neonates, some strains have been demonstrated to be beneficial as probiotics. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 85 publications
(192 reference statements)
0
25
0
Order By: Relevance
“…Dietary supplementation with probiotics is considered as an important way to enhance the intestinal health in fish [15]. Clostridium butyricum (CB) is a gram-positive obligate anaerobic bacillus, which exhibits positive effects on inhibition of inflammatory response and reparation of intestinal epithelium and reduction of pathogenic bacteria [16,17]. In recent years, CB has been carried out in human, terrestrial, and some aquatic species to increase growth performance, promote nutrient utilization efficiency, maintain intestinal morphology, and improve disease resistance [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation with probiotics is considered as an important way to enhance the intestinal health in fish [15]. Clostridium butyricum (CB) is a gram-positive obligate anaerobic bacillus, which exhibits positive effects on inhibition of inflammatory response and reparation of intestinal epithelium and reduction of pathogenic bacteria [16,17]. In recent years, CB has been carried out in human, terrestrial, and some aquatic species to increase growth performance, promote nutrient utilization efficiency, maintain intestinal morphology, and improve disease resistance [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many studies have indicated that probiotic treatment in the early life is necessary for digestive physiology functions, gastrointestinal tract immune and microbiota development (8,9). Clostridium butyricum (CB) is a grampositive, obligate anaerobic and endospore-forming probiotic, which is part of the normal gut bacteria for both mammals and aquatic animals (10,11). CB could improve gastrointestinal function, which has been used for the clinical treatment of newborn animals (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…, Roeselers et al, 2011 ; Gajardo et al, 2016 ; do Vale-Pereira et al, 2017 ; Rimoldi et al, 2019 ; Ruzauskas et al, 2021 ). Although it is hard to predict physiological roles for these microbes, some bacteria of the genera Staphylococcus , Vibrio , and Aeromonas can be opportunistic pathogens, while others have been used as probiotics in fish diets promoting positive immune and growth responses ( Austin et al, 1995 ; Taoka et al, 2006 ; Pieters et al, 2008 ; Abd El-Rhman, Khattab & Shalaby, 2009 ; Korkea-aho et al, 2012 ; Gao et al, 2016 ; Qi et al, 2020 ; Tran et al, 2020 ). Undibacterium spp.…”
Section: Discussionmentioning
confidence: 99%